The Serendipity Case of the Pedunculopontine Nucleus Low-Frequency Brain Stimulation: Chasing a Gait Response, Finding Sleep, and Cognition Improvement - Stefani, Alessandro (Frontiers Media S.A., 2013)
Deep brain stimulation (DBS) of the subthalamic nucleus (STN) is an efficacious therapy for Parkinson’s disease (PD) but its effects on non-motor facets may be detrimental. The low-frequency stimulation (LFS) of the pedunculopontine nucleus (PPN or the nucleus tegmenti pedunculopontini – PPTg-) opened new perspectives. In our hands, PPTg-LFS revealed a modest influence on gait but increased sleep quality and degree of attentiveness. At odds with potential adverse events following STN-DBS, executive functions, under PPTg-ON, ameliorated. A recent study comparing both targets found that only PPTg-LFS improved night-time sleep and daytime sleepiness. Chances are that different neurosurgical groups influence either the PPN sub-portion identified as pars dissipata (more interconnected with GPi/STN) or the caudal PPN region known as pars compacta, preferentially targeting intralaminar and associative nucleus of the thalamus. Yet, the wide electrical field delivered affects a plethora of en passant circuits, and a fine distinction on the specific pathways involved is elusive. This review explores our angle of vision, by which PPTg-LFS activates cholinergic and glutamatergic ascending fibers, influencing non-motor behaviors.